Rural Areas And Agriculture In Poland Versus Some Legal Aspects Of Nature Conservation - Kamila MUSIAL (Communications of International Proceedings, 2023)
The paper presents issue of some legal aspects of nature conservation as expression of the protection of rural areas in Poland. The directions of development of such areas in the European Union countries were described in the Cork Declaration adopted in 1996. Nowadays, the EU operates within the framework of uniform legal regulations, and is obliged to implement the provisions of the new CAP, including the strategy of the program called the Green Deal. In the latter there was paid much attention to the issues of environmental protection and nature conservation, which had had no precedent before. Moreover, the solution to problems of nature conservation for the first time has been entrusted to farmers and agriculture in general. It may be particularly important for Polish agriculture, as a significant part of the biodiversity depends on traditional farming systems. However, at present they are either under pressure from agricultural intensification or land abandonment, which both are not beneficial for sustainable development of the rural areas.
Keywords: forms of nature conservation; legal acts; agriculture; cultural landscape; sustainable development